The Role of Customer Satisfaction in Mediating the Influence of Product Quality, Service Quality, and Brand Image on Repurchase Intention - Devi, Dewa Ayu Yunia; Darma, Gede Sri (International Journal of Science and Society, 2024)
Nowadays, the trend of cosmetic usage is not only significant for women, but men have also become a substantial segment of the cosmetic market. “Along with this, maintaining consumer loyalty has become a major challenge for many companies. Previous studies have examined the factors influencing repurchase intention, but there has been no research on the role of consumer satisfaction in mediating the influence of these factors. Empirical data were gathered using questionnaires provided to 168 respondents and analyzed using the Structural Equation Modeling (SEM) approach with SmartPLS. The findings of this study demonstrate that consumer satisfaction can strengthen the connection between product quality, service quality, and brand image and their influence on repurchase intention. These findings are expected to provide valuable contributions to cosmetic industry players in formulating effective strategies to enhance customer satisfaction and promote purchase loyalty.” This study is also anticipated to serve as a valuable resource for future researchers who aim to explore and analyze the various factors that impact consumers' intention to make repeat purchases within the cosmetics industry.